1981
DOI: 10.1246/bcsj.54.138
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation-Reduction Properties of Mixed Oxides in the Cerium–Uranium–Oxygen System

Abstract: The formation and the oxidation-reduction properties of mixed oxides in the Ce–U–O ternary system were examined by means of thermogravimetry and the X-ray diffraction technique. The mixed oxides were prepared by the reactions of CeO2 with U3O8 in air and in hydrogen. The composition of the products heated in air, followed by slow cooling to room temperature, was approximately expressed by this equation: yCeO2+(1–y)UO2.67. By X-ray diffraction, it was shown that the oxides formed at 1100 °C in air were mixtures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…The XRD pattern of the oxidized product corresponding to the compositions of 8.5, 16.0 and 31.3 mol% Ce (100 AE Ce/(U + Ce)) was found to be a mixture of orthorhombic and cubic phases. The segregation of MO 2þx (M ¼ (U + Ce)) cubic phase observed during the oxidation of the mixed oxide containing 8.5 mol% Ce is in agreement with the results of Tagawa and Fujino [38] and is in contrast to the results reported by Nawada et al [32] wherein the limit of the M 3 O 8 singlephase region was found to be close to 12 mol% Ce. The phase separation observed in this study can be attributed to the long duration (24 h) of annealing of the sample in air as compared to 8-10 h reported in the earlier study [32].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The XRD pattern of the oxidized product corresponding to the compositions of 8.5, 16.0 and 31.3 mol% Ce (100 AE Ce/(U + Ce)) was found to be a mixture of orthorhombic and cubic phases. The segregation of MO 2þx (M ¼ (U + Ce)) cubic phase observed during the oxidation of the mixed oxide containing 8.5 mol% Ce is in agreement with the results of Tagawa and Fujino [38] and is in contrast to the results reported by Nawada et al [32] wherein the limit of the M 3 O 8 singlephase region was found to be close to 12 mol% Ce. The phase separation observed in this study can be attributed to the long duration (24 h) of annealing of the sample in air as compared to 8-10 h reported in the earlier study [32].…”
Section: Resultssupporting
confidence: 91%
“…In the case of U 0:915 Ce 0:085 O 2:67 , the U 4f 7=2 peak appeared at 380.9 eV of which the value is less than that of U(VI) in UO 3 [38] and more than that of U(V). Hence, U in this oxide exhibits an oxidation state higher than that in U 3 O 8 and lower than the one in UO 3 , which also supports the O/M result.…”
Section: Resultsmentioning
confidence: 89%
“…Nevertheless, while the values published by Tagawa et al . remained close to the Vegard’s law, those from Lorenzelli and Touzelin appeared to be strongly different and might probably be considered with caution (Figure a). Also, it is important to note that when the amount of cerium incorporated in the samples increased (typically, x Ce > 0.60), the unit cell parameter got closer to the Vegard’s law, indicating almost negligible deviation from the stoichiometry despite the conditions applied.…”
Section: Results and Discussionmentioning
confidence: 90%
“…Variation of the unit cell parameters of U 1– x Ce x O 2±δ reported in the literature for (a) sub-stoichiometric samples with O/M < 2.00 (black square: Lorenzelli and Touzelin, blue triangle: Tagawa et al, and red circle: Markin et al); (b) stoichiometric samples with O/M = 2.00 (black square: Dorr et al, red circle: Krishnan et al, blue triangle: Martin et al, pink star: Krishnan et al, blue inverted triangle: Nagarajan et al, pink diamond: Kim et al, violet triangle: Cao et al, orange triangle: Markin et al, yellow hexagon: Kurosaki et al, green pentagon: Designan et al, blue hollow circle: Prieur et al, and brown hollow circle: Zinkevich et al; and (c) hyper-stoichiometric samples with O/M > 2.00: Nawada et al (black square: 873 K), (red circle: 1123 K), (blue triangle: 1273 K); green inverted triangle: Markin et al; and violet diamond: Tagawa et al The dashed lined represents the Vegard’s law extrapolated from pure UO 2 and CeO 2 data.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation